CASE STUDY in the system of a professionally-oriented foreign language teaching at higher school - Olga V. Igumnova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
Foreign language at higher school reflects the specific of the students’ forthcoming professional activity. Decade-old publications prove the need of including case study in a foreign language teaching, the stages of working with the case are revealed. However, the case study method will promote the language teaching effectiveness, if a student is ready to work with cases. The purpose of this paper is to indicate the possible consistency of the methods of teaching a professionally-oriented foreign language at junior courses of non-linguistic universities, as well as the place of the case study in them from the point of view of the effectiveness of its application. When writing the paper, such theoretical research methods as analysis, synthesis, systematization, generalization, abstraction, design and modeling of the educational process as well as case study application evaluation criteria were used. Such an approach to the generalization of private teaching experience makes it possible to identify pedagogical conditions of case study application efficiency in teaching and learning activities, to specify the strategic and tactical language learning process design with cases in mind and to present the modeling of teaching within one topic. The author agrees that the case study allows assessing the students’ level of foreign language competence formation. At the same time, it is noted that the case study application evaluation should consist of components that track the overall curricular actions of the language trainer from the beginning to the completion of the study of the topic. In this regard, it is necessary to evaluate the quality of the case analysis completed by students, the availability, logic, consistency and literacy of their statement of the case issues, as well as the ability to operate the actual material studied within the topic, students’ readiness for dialogue and the use of compensatory skills to realize their own communicative intention. The proposed criteria and stages of modeling teaching and learning activities can be used in practice.